CYTOMORPHOLOGICAL CHANGES IN MESONEPHROS AND BLOOD OF PERCH INFESTED WITH DIPHYLLOBOTRIUM LATUM INFESTATION (PERCA FLUVIATILIS,LINNAEUS, 1758) (Experimental biology, 2024)
The article describes changes in the cell composition of mesonephros and immunocompetent organs and tissues of perch fish infected with Diphyllobotrium latum infestation (Perca fluviatilis, Linnaeus, 1758). The aim of the study is to identify the immune mechanisms of fish infected with parasitic diseases. In laboratory conditions, blood and kidney body part markings (mesonephros) were examined. The blood of the caught fish was taken from a blood vessel after a caudoectomy. Leukocytes, the main influential cells of the immune system of fish responsible for invasion. It has been proven that leukocytes are formed in the immune organs of fish , circulating in the channel of blood vessels, ensuring the development of an innate and adaptive immune response to antigenic influences. It has been experimentally established that the larval plerocercoid stage of diphyllobotriosis infestation contributes to a decrease in the efficiency of Leukocyte production in the organs of hematopoiesis of perch fish, the occurrence of morphofunctional disorders. It has been described that the growth and vital activity of the hosts of parasites in the intestinal channel leads to inflammation of the mucous membrane of their internal organs, dysfunction of hollow organs. Plerocercoids of diphyllobotria, as a multicellular organism that carries foreign antigens for the host in its cells, are capable of generating an immune response in the body of fish. Despite the immune response, the plerocercoids of the parasite develop in the host organism and grow into an adult parasite. It has been found that parasites have a direct and indirect immunomodulatory effect on the host’s body. Data on morphophysiological, hematological and immunological parameters of diphyllobotrium latum plerocercoids caused in the body of perch fish, pathogenic effects on cavity organs are given. The results obtained showed, on the one hand, the involvement of the mesonephros of perch in the immune response, and on the other – the low adaptive capabilities of the hematopoietic organs that form immunological homeostasis.
Keywords: invasive diseases, tapeworms, mesonephros, leukocyte composition of blood, plerocercoid, imago, immune response to parasites, parasite-host relations, proliferation, leukopenia, hematopoiesis